When a lesbian dies: An analysis of the media approach and lesboodio in Chile (2018-2021). (Polis (Santiago), 2023)
Where is the L? Some lesbofeminists manifest after the 9 lesbicides in the last decade, the low visibility of the media and the normalization of hate speech about sexual diversity. Despite the fact that the literature has expressed the role of the press in the reproduction of stigmas and the generation of insecurities, a less studied topic is its relationship with the receptions and responses of people to news about lesboodio. Within the framework of this problem, this study intends to analyze how the media coverage around the acts of violence against lesbian women and the public responses to these news between the years 2018-2021 in Chile are related. To do this, a mixed content analysis was carried out, which consisted both in the quantification and in the qualitative understanding of the elements present in the news and in the comments of the news events of violence against lesbian women, of the internet portals Emol and Bío-Bío. The findings indicate that the news message provides the receivers with an interpretative framework that guides the receiver and gives him the elements to consider in the public debate on these facts, thus reproducing forms of violence against lesbian women; blaming, questioning and denying lesboodio as a social problem.
Keywords: Lesboodio; media approach; public responses; violence